Electron-phonon interaction and structural changes in the electronically excited state of WO3 photocatalyst - Kaneko, Masanori; Nozawa, Shunsuke; Yamashita, Koichi (Frontiers in Energy Research, 2022)
The structural changes in the electronically excited state of tungsten oxide (WO3), a promising visible-light-responsive photocatalyst, are discussed from the viewpoint of carrier-phonon interactions using first-principles calculations. The increase in the pre-edge peak observed immediately after photoexcitation by high-speed time-resolved X-ray absorption spectroscopy is attributed to the local lattice distortion due to Fröhlich-Polaron generation by the interaction with optical longitudinal phonons. Bimolecular recombination could be suppressed by the formation of bipolaron states, and high internal quantum yields in photocatalysis are expected. The bipolaron states are unstable states in the electronically excited state, and relax to stable structures in the electronically excited state by phonon-phonon interaction. In the stable structure, the transition dipole moment is found to be nearly zero, suggesting a non-radiative transition to the electronic ground state and a long lifetime in the electronically excited state.